Efficiently non-authenticated group key management protocol withstand interruption attack - XU Peng1; CUI Guo-hua1; ZHENG Ming-hui2 (Tongxin xuebao)
To overcome the fault that the interruption attack from internal participation of BD3 protocol, a new scheme was constructed by applying the bilinear map and had the provable security with tight reduction. By analyzing and simulating, compared with another scheme, it was obvious that the new scheme was more efficiently than that one. Especially in the quantity of message for communication, it could be approximately 0.14 multiple of that one. On the other hand, the process of simulation simply explaines the method how to carry out the bilinear map, especially how to choose the parameters of it and its signification in the security.